Does the reticulin binding property of cereal proteins demonstrable in vitro have pathogenetic significance for coeliac disease?. Issue 11 (November 1985) - Unsworth, D J; Holborow, E J
Abstract : We used an indirect immunofluorescence technique, using rabbit antisera against cereal protein extracts, to determine which cereal proteins bind to reticulin in tissue sections and which do not. Wheat albumin extracts and globulins and gliadin extracts from a range of different wheat varieties, and prolamine extracts of barley and rye each bound to reticulin in vitro, while prolamine extracts of maize and rice did not. Wheat gluten subfractions were also tested. Subfractions B and C and subfractions B2 and B3 did bind, but fraction A and subfraction B1 did not. The results suggest an association between in vitro reticulin binding and the ability to induce gluten sensitive enteropathy on feeding.